Fear and loathing in Las Vegas : a savage journey to the heart of the American dream - Thompson, Hunter S. (London : Vintage Books, 1998)
This cult classic of gonzo journalism is the best chronicle of drug-soaked, addle-brained, rollicking good times ever committed to the printed page. It is also the tale of a long weekend road trip that has gone down in the annals of American pop culture as one of the strangest journeys ever undertaken.
Keywords: Thompson, Hunter S; Journalists -- United States -- Biography